Integrating the study of criminal justice and literature - Hirschel, J. David (American journal of criminal justice, 1982)
The best interdisciplinary courses are those that not only expand a student’s consciousness but also increase a student’s options. A course in criminal justice and literature can give criminal justice students a broader philosophical basis for work in their profession and metaphors for understanding their discipline. For humanities students, it can reveal the extent to which literature reflects social conditions and criminal justice theories and practices. With this in mind, the authors, professors of criminal justice and English, respectively, designed and taught an experimental course that integrates topics in criminal justice with topics in literature. This article details the philosophies and goals behind this undertaking and describes the specific course objectives, readings and other instructional materials used, and the teaching methods and evaluation procedures employed. Also included are the results of a research survey which explored student perceptions of and reactions to the course. The article concludes by offering suggestions and cautionary advice that would be helpful for those interested in setting up such a curriculum.